Effects of Dietary Zymosan-A on the Growth Performance and Intestinal Morphology, Digestive Capacity, and Microbial Community in Litopenaeus vannamei - Zheng, Yudong; Hou, Cuihong; Yan, Zhao; Chen, Jian; Wang, Hongming; Tan, Beiping; Zhang, Shuang (Frontiers in Marine Science, 2022)
The effects of dietary zymosan A on the growth performance and histological structure, digestive capacity, and microbiota were investigated in Litopenaeus vannamei, an important shrimp species used in aquaculture. L. vannamei (initial body weight = 0.41 ± 0.05 g) were fed diets supplemented with zymosan-A at doses of 0 mg/kg (Z0, control), 1 mg/kg (Z1), 5 mg/kg (Z5), 25 mg/kg (Z25), 125 mg/kg (Z125), or 625 mg/kg (Z625) for 8 weeks. The results showed that doses of 25 and 125 mg/kg significantly increased the final body weight, weight gain rate (WGR), and specific growth rate (SGR) and significantly decreased the feed conversion rate compared with the controls (p < 0.05). Analyses of the WGR and SGR revealed that the optimum dietary zymosan-A levels were 308.56 and 300.00 mg/kg, respectively. Compared with the controls, the intestinal villus height was significantly increased by the addition of zymosan-A at doses ≥25 mg/kg (p < 0.05). An obvious upregulation of the activities of trypsin and amylase was observed in all groups that received zymosan-A supplementation, while the activity of lipase was significantly increased in groups Z125 and Z625 (p < 0.05). Consistently, the gene expressions of trypsin and lipase were significantly higher in group Z125, while the gene expression of amylase was significantly increased in all zymosan-A-supplemented groups (p < 0.05). Analysis of the intestinal microbiota showed significant differences in the alpha diversity between group Z125 and controls. The supplemented groups showed altered intestinal bacterial community structures and compositions at the phylum, family, and genus levels, with statistical differences observed in the relative abundances of some dominant species. Tax4Fun predictions of the microbiota indicated that multiple intestinal functions were significantly altered in all zymosan-A-supplemented groups, except Z1. Among these groups, the functions related to transport and catabolism, substance dependence, cardiovascular disease, and signaling molecules and interactions were obviously increased by the addition of zymosan-A at different levels. In conclusion, dietary supplementation of the optimum amount of zymosan-A can improve growth and intestinal function in L. vannamei, which will be valuable in aquaculture.